Effects of 17?-Estradiol and Vitamin E Treatments on Blood Trace Element and Antioxidant Enzyme Levels in Ovariectomized Rats - Ulas, Mustafa; Cay, Mehmet (Humana Press Inc, 2011)
We investigated the effect of 17 beta-estradiol (E-2) alone and separately vitamin E treatment on trace element status of rats following an ovariectomic operation. Forty rats were equally divided into four groups: Group 1, control, non-ovariectomized rats; Group 2, (OVX) rats, ovariectomized under general anesthesia; Group 3, (OVX+E-2) rats, the group received a 40 A mu g kg(-1) subcutan dose of E-2 per day after ovariectomy; and Group 4, (OVX + E-2 + vitamin E) rats, received the same E-2 treatment, but with an additional 100 mg kg(-1) intraperitoneal dose of vitamin E per day after ovariectomy. At the end of the 30-day experiment, the rats were sacrificed and their blood was collected for the measurement of zinc, copper, iron, phosphorus, selenium, magnesium, calcium, manganese, and chromium; copper-zinc superoxide dismutase (SOD); manganese-superoxide dismutase (Mn-SOD); glutathione peroxidase (Se-GSH-Px); and catalase (CAT). The levels of zinc, copper, iron, phosphorus, selenium, calcium, chromium, and manganese and activities of SOD, Mn-SOD, Se-GSH-Px, and CAT were lower in the OVX than in the control group, but magnesium level was unaffected. However, zinc, copper, iron, phosphorus, selenium, calcium, chromium, and manganese levels and SOD, Mn-SOD, Se-GSH-Px, and CAT activities were higher under separate E-2 and E-2 + vitamin E treatments. The level of magnesium in the treated-OVX groups was not different than in the OVX group. In conclusion, E-2 treatment has an ameliorating effect on the trace element status in OVX, and this effect may be enhanced with the addition of vitamin E.
Keywords: Ovariectomy; 17 beta-estradiol; Vitamin E; Zinc; Iron; Copper